The material life of human beings : artifacts, behavior, and communication - Schiffer, Michael B. (Michael Brian), 1947- (Routledge, 1999)
Through a broad range of examples, the author demonstrates how theories of behaviour and communication have too often ignored the fundamental importance of objects in human life.